A review of semi-volatile organic compounds (SVOCs) in the indoor environment: occurrence in consumer products, indoor air and dust. (June 2018) - Lucattini, Luisa; Poma, Giulia; Covaci, Adrian; de Boer, Jacob; Lamoree, Marja H.; Leonards, Pim E.G.
Abstract: As many people spend a large part of their life indoors, the quality of the indoor environment is important. Data on contaminants such as flame retardants, pesticides and plasticizers are available for indoor air and dust but are scarce for consumer products such as computers, televisions, furniture, carpets, etc. This review presents information on semi-volatile organic compounds (SVOCs) in consumer products in an attempt to link the information available for chemicals in indoor air and dust with their indoor sources. A number of 256 papers were selected and divided among SVOCs found in consumer products (n = 57), indoor dust (n = 104) and air (n = 95). Concentrations of SVOCs in consumer products, indoor dust and air are reported (e.g. PFASs max: 13.9 μg/g in textiles, 5.8 μg/kg in building materials, 121 ng/g in house dust and 6.4 ng/m 3 in indoor air). Most of the studies show common aims, such as human exposure and risk assessment. The main micro-environments investigated (houses, offices and schools) reflect the relevance of indoor air quality. Most of the studies show a lack of data on concentrations of chemicals in consumer goods and often only the presence of chemicals is reported. At the moment this is the largest obstacle linking chemicals in products to chemicals detected in indoor air and dust. Graphical abstract: Image 1 Highlights: Information on semi-volatile organic compounds (SVOCs) in consumer products, indoor air and dust was reviewed. Limited data on concentrations of SVOCs in consumer goods is available, mainly their presence is reported. The largest obstacle linking SVOCs in products to indoor air/dust ones is the lack on SVOC concentrations in consumer goods.